Use of HH micromixer for the production of PBCA microparticles by emulsion polymerization toward cosmetic application - Vieira, Aline Rocha (2024)
Different methods of reaction control for the production of poly (butyl cyanoacrylate) microparticles have been studied, always considering pH and the monomer-to-initiator ratio. However, multiple process steps and reagents are required. Therefore, a microfluidic micro-mixer with HH geometry was employed, varying flow parameters, channel quantity, and residence time of the formulation in the system to regulate the emulsion polymerization reaction and formation of PBCA microparticles. Thus, the microparticles were synthesized via anionic emulsion polymerization (A/O) using a microfluidic system comprising a microfluidic device with an HH geometry micromixer consisting of 15-channels in LTCC, enabling synthesis in a single step. Total flow rates of 39 and 78 mL·min-1 exhibited superior results for microparticles formation. The microparticles were characterized for their morphology, demonstrating average diameter values. For the 45/55 (w/o) ratio with 19.2% (w/w) n-BCA, the average diameter was 642 nm, while for 20/80 (w/o) with 5.0% n-BCA, it was 74 µm. The microparticles exhibited spherical formation, comprising the PBCA polymer as confirmed by FTIR analyses.